Resiliensi SME di Sektor Ekonomi Kreatif: Pelajaran dari Era Pasca-Pandemi COVID-19 - Zaky Al Hakim, Muhammad Rayhan; Nisa, Fauzatul Laily (Jurnal Ekonomika : INDEPENDEN, 2024)
This study examines the concept of resilience among Small and Medium Enterprises (SMEs) in the creative economic sector, particularly in the context of challenges posed by the COVID-19 pandemic. Utilizing qualitative methods and literature review, this research explores the definition of resilience, the impact of the pandemic on SME resilience, and the strategies needed. The findings indicate that product diversification and human resource empowerment are key strategies to strengthen resilience. Additionally, both internal and external factors influence the adaptability of SMEs. Case studies on SMEs such as Airy Rooms and UHT milk producers illustrate the contrast between success and failure in facing the crisis. The study concludes that SME resilience is not only crucial for the continuity of the business but also for broader economic stability in the face of global disruptions.